2003
DOI: 10.5860/lrts.47n1.16
|View full text |Cite
|
Sign up to set email alerts
|

Use and Perception of the DCRB Core Standard

Abstract: B ibliographic control of rare book collections has always been a time-consuming and specialized process. The materials in special collections are there for particular and compelling reasons. Catalogers of such collections have traditionally identified those special attributes in catalog records with full-level bibliographic description, extensive notes, and as many access points as are deemed appropriate by both catalogers and curators. The new edition will include rules for the various formats of materials. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…In order to determine if size of collection, existence of backlogs, number of rare book catalogers, and reporting structure correlated to adoption of the Descriptive Cataloging of Rare Books core standard for bibliographic records, M. Winslow Lundy surveyed a group of heads of cataloging, heads of special collections, and special collections catalogers at ARL libraries, along with other targeted groups. 12 In thirty-seven responses, she found a range of staffing for catalogers between 0.25 FTE to 9 FTE, although only a small number of institutions have more than one FTE rare book cataloger. Regarding administrative structure, she found that a slightly higher number of institutions have rare book catalogers report to cataloging or technical services units (n = 19) than to special collections departments (n = 12), while six institutions reported catalogers with split reporting lines.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In order to determine if size of collection, existence of backlogs, number of rare book catalogers, and reporting structure correlated to adoption of the Descriptive Cataloging of Rare Books core standard for bibliographic records, M. Winslow Lundy surveyed a group of heads of cataloging, heads of special collections, and special collections catalogers at ARL libraries, along with other targeted groups. 12 In thirty-seven responses, she found a range of staffing for catalogers between 0.25 FTE to 9 FTE, although only a small number of institutions have more than one FTE rare book cataloger. Regarding administrative structure, she found that a slightly higher number of institutions have rare book catalogers report to cataloging or technical services units (n = 19) than to special collections departments (n = 12), while six institutions reported catalogers with split reporting lines.…”
Section: Literature Reviewmentioning
confidence: 99%
“…12 In thirty-seven responses, she found a range of staffing for catalogers between 0.25 FTE to 9 FTE, although only a small number of institutions have more than one FTE rare book cataloger. Regarding administrative structure, she found that a slightly higher number of institutions have rare book catalogers report to cataloging or technical services units (n = 19) than to special collections departments (n = 12), while six institutions reported catalogers with split reporting lines.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An investigation of this response was researched and analyzed in "Evidence of Application of the DCRB Core Standard in WorldCat and RLIN." 12 Schuitema provided a lengthy introduction of the core bibliographic record and what it is, where the standard originates, and how the core level is different from the full level. 13 She also addressed the issues that are associated with the implementation of the core record and examined some of the reasons libraries are implementing the core standards.…”
Section: Introductionmentioning
confidence: 99%